Can European sea bass (Dicentrarchus labrax) scale be a good candidate for nano-bioceramics production? - (:unkn) unknown (Trans Tech Publications Ltd, 2016)
Bioceramics are commonly used biomaterials for orthopedic and dental applications. Among these bioceramics, hydroxyapatite (HA) and tricalcium phosphate (TCP) are of interest and are used in various biomedical applications. Production of bioceramics from natural materials such as bovine and sheep bones with calcination method, is possible. Lately, fish scales become an alternative biological source for bioceramic production. The present study proposes an approach to obtain HA bone-scaffolds from European Sea Bass (Dicentrarchus labrax) scales aiming to provide nano-biomaterials via calcination method. Untreated fish scales are obtained and are carefully cleaned from their meat and grease. They are washed with alkaline water several times and calcinated at 850°C for 4 hours. Energy Dispersive Spectroscopy (EDS), X-ray diffraction analysis, Scanning Electron Microscopy (SEM) studies are performed. Various calcium phosphate species (HA, TCP) are identified in the study. SEM images prove the presence of the nano-scale structures. This study indicates calcination as a simple way of nano-scale bioceramic production for drug delivery and tissue engineering applications. Being produced from wastes of a sustainable and cheap source, these bioceramics can be good candidates for future clinical applications. © 2016 Trans Tech Publications, Switzerland.
Keywords: Biological hydroxyapatite; Calcination; Fish scales; Simple production; Waste materials